The effectiveness of the five-step strategy (SQ3R) in developing reading comprehension skills for sixth grade primary school students - Al-Ghamdi, Khaled Mohammed (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to measure the effectiveness of the five-step strategy (SQ3R) in developing reading comprehension skills, and knowing the necessary reading comprehension skills for sixth graders. To achieve the goal of the study, the researchers used the semi-experimental approach, which is based on the experimental and control groups, and use the pre-measurement to control the experimental procedures, then the post-measurement to study the differences and their significance between the experimental group. The researchers designed a number of research materials and tools: Reading comprehension skills list, Reading comprehension skills test, Learner's Guide to Implementing the Five-Step Strategy (SQ3R). The study was applied to a random sample consisting of 60 students from the sixth regular primary school students in the academic year 1441 H - 2019 at Prince Saud bin Abdul Mohsen Elementary School in Jeddah, they were divided into two equal groups (30) students, one is experimental and the other is a control. The study reached the following results: There were statistically significant differences at the level of a
Keywords: Reading comprehension; (SQ3R); reading comprehension skills; primary school; Saudi education